Central Nervous System Lymphoma: The Great Mimicker—A Single-Institution Retrospective Study - Danielle A. Bazer; Ewa Zabrocka; Nicholas Koroneos; Agnieszka Kowalska (Case Reports in Oncological Medicine)
Background. Primary central nervous system lymphoma (PCNSL) is a rare, aggressive form of non-Hodgkin lymphoma contained in the brain and the spinal cord as well as the meninges, cranial nerves, eyes, and cerebrospinal fluid (CSF). Due to its variable presentation and lack of associated B-symptoms, it is quite challenging to diagnose PCNSL, if there is not a high level of suspicion. Methods. This is a retrospective case series examining 13 human immunodeficiency virus- (HIV-) negative patients with PCNSL and DLBCL type, with a median age of 75 years old. Results. The most common presenting symptom was altered mental status. The frontal lobes, basal ganglia, cerebellum, and corpus callosum were most affected. Prior to brain biopsy, 4/13 patients were on steroids, which did not affect biopsy results and the average time to diagnosis was 1 month. 9/13 patients who did not receive steroids had an average time to diagnosis of less than 1 month. Conclusion. Although steroid administration did not appear to diminish the yield of the biopsy, it is a best practice to withhold steroids prior to biopsy to decrease the time to diagnose PCNSL.